Practice Variation in Validation of Device Denominator Data for National Healthcare Safety Network Reporting. (October 2020) - Challener, Douglas; Sampathkumar, Priya; O'Horo, John O
Abstract : Background: The NHSN is a widely used CDC program for tracking healthcare-associated infections (HAIs). The goal of the NHSN is to help healthcare organizations to identify and track the incidence of HAI and to prevent adverse events as well as to simplify mandatory quality reporting to the CMS. Healthcare organizations provide both event data for HAIs and information about the population at risk. For device-related infections, device denominator data (eg, data related to urinary or intravascular catheters, and ventilators) must be collected and reported. NHSN guidelines require that electronic reporting of device denominator numbers be validated to be within 5% of manually collected counts over a period of 3 consecutive months. Little is known about current practical application of validation practices. Methods: We surveyed members of the SHEA Research Network (SRN) to assess awareness of and compliance with the current NHSN requirements for device denominator data validation. Results: The survey was sent to 89 member institutions of the SRN from November 20, 2018, to December 12, 2018. The response rate was 35.7%, and 90% of respondents are currently using an electronic system for device denominator count reporting. All except 1 institution manually validated the data. Of the facilities that had completed validation, 31% used <90 days of manual data. Moreover, 82% of these facilities found a difference of <5% between the electronic data and manual data without a statistically significant difference between those with at least 90 days of validation data and those with <90 days. Also, 21% of facilities validated data based on a subset of units. Conclusions: Although most respondents to the survey validate electronically collected device denominator data in accordance with NHSN's requirements, nearly one-third reported using shorter validation periods than NHSN requires. However, shorter periods were not associated with worse concordance. The NHSN should evaluate whether the burden of a 3-month validation period is justified. Funding: None Disclosures: None